2013
DOI: 10.1111/jne.12021
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin in the Central Amygdaloid Nucleus Modulates the Neuroendocrine Responses Induced by Hypertonic Volume Expansion in the Rat

Abstract: The present study investigated the involvement of the oxytocinergic neurones that project into the central amygdala (CeA) in the control of electrolyte excretion and hormone secretion in unanaesthetised rats subjected to acute hypertonic blood volume expansion (BVE; 0.3 M NaCl, 2 ml/100 g of body weight over 1 min). Oxytocin and vasopressin mRNA expression in the paraventricular (Pa) and supraoptic nucleus (SON) of the hypothalamus were also determined using the real time-polymerase chain reaction and in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…It has been observed that isotonic volume expansion by intra-atrial injection of isotonic saline induced a rapid increase in plasma oxytocin and ANP concentrations and a concomitant decrease in plasma vasopressin concentration, and that oxytocin (I.P.) injected caused a significant increase in urinary osmolality, natriuresis and plasma ANP level [28]. Because it is known that loss of blood volume stimulates release of vasopressin from hypothalamus-pituitary, which decreases release of ANP from atria.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that isotonic volume expansion by intra-atrial injection of isotonic saline induced a rapid increase in plasma oxytocin and ANP concentrations and a concomitant decrease in plasma vasopressin concentration, and that oxytocin (I.P.) injected caused a significant increase in urinary osmolality, natriuresis and plasma ANP level [28]. Because it is known that loss of blood volume stimulates release of vasopressin from hypothalamus-pituitary, which decreases release of ANP from atria.…”
Section: Editorialmentioning
confidence: 99%
“…Because it is known that loss of blood volume stimulates release of vasopressin from hypothalamus-pituitary, which decreases release of ANP from atria. It has been hypothesized that volumeexpansion stimulates release of neuropeptide oxytocin from hypothalamus-pituitary into blood, which circulated to the atria to stimulate ANP release and promote natriuresis [28]. Therefore, a dedicated balance between two neuropeptides released from hypothalamus-pituitary may be critical for maintenance of body volume homeostasis and blood pressure regulation.…”
Section: Editorialmentioning
confidence: 99%